Karakteristik Parameter Kuat Geser Tanah pada Lereng Akibat Perubahan Kadar Air Tanah - Amalia, Ghina; Minaka, Utari Sriwijaya; Aprilianda, Aprilianda (Jurnal Teknik Sipil, 2025)
The slope failure that occurred on the slope is indicated to be caused by an increase in soil mass due to the increase in water content filling the soil pores, which affects the soil properties, especially shear strength as one of the mechanical properties of soil. This study aims to analyze the effect of changes in soil water content on the shear strength of the slope. The study used disturbed soil samples taken at the edge of the slope on the Manna-Pagaralam Road section and were dried. Compaction testing was conducted to obtain the optimum water content (OWC) value, which represents the middle value of the variation in soil water content in the test samples. The variation of the test samples includes OWC-20%OWC, OWC-10%OWC, OWC, OWC+10%OWC, and OWC+20%OWC. The shear strength of the soil was obtained through Direct Shear testing. According to the USCS standard, the soil is classified as sandy clay soil. The Direct Shear testing results showed the highest cohesion (c) value in the OWC variation or at the Optimum Water Content variation, which is 2.796 kPa. This is because the cohesion value occurs in the fine particles, namely clay, which is influenced by the intergranular water content. Meanwhile, the highest internal friction angle value was obtained in the OWC-10%OWC variation, which is 32.15o. This is because the internal friction angle value occurs in the coarse particles, namely sand particles, where friction decreases as the water content filling the soil pores increases.